ANTHRACNOSE DISEASE ON VEGETABLES CROPS IN SERANG VILLAGE, DISTRICT OF KARANGREJA, PURBALINGGA REGENCY - Sucianto, Eddy Tri; Abbas, Muachiroh; Purwati, Endang Sri (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2020)
Various vegetables are widely cultivated in Serang Village, District of Karangreja, Purbalingga Regency. This village is located at 1350 above sea level. Vegetable productions in Serang are often constrained by the presence of diseases caused by pathogenic fungi Colletotrichum sp. called anthracnose. However, there was no data regarding anthracnose attack in vegetable crops in Serang. This study aimed to find out the types of vegetable that were attacked by anthracnose disease as well as the intensity of the attack in a vegetable crops in Serang Village, Karangreja District, Purbalingga Regency. Vegetables with anthracnose were purposively selected from 10 different locations. The anthracnose disease was identified based on their symptoms and analyzed descriptively. The results showed that five different vegetable crops suffer from anthracnose, and the intensity of anthracnose ranges from 32% up to 52%. Those intensity percentages indicate that large part of vegetable crops in Serang Village was attacked by anthracnose and possibly cause a significant decrease in vegetable production in that village. Our results provide the first scientific data about anthracnose attack in Serang Village. The data is essential for the management of vegetable crops in Serang Village.